Biomass enhancement and activation of transcriptional regulation in sorghum seedling by plasma-activated water - Beak, Hong Kwan; Priatama, Ryza A.; Han, Sang-Ik; Song, Ilchan; Park, Soon Ju; Lee, Young Koung (Frontiers in Plant Science, 2024)
Introduction Recent advancements in agricultural technology have highlighted the potential of eco-friendly innovations, such as plasma-activated water (PAW), for enhancing seed germination, growth, and biomass production. Methods In this study, we investigated the effects of PAW irrigation on young sorghum seedlings through phenotypic and transcriptional analyses. We measured growth parameters, including seedling height, stem thickness, and biomass, across five sorghum varieties: BTx623, Sodamchal, Noeulchal, Baremae, and Hichal. Additionally, we performed detailed analyses of stem cross-sections to evaluate the structural changes induced by PAW. Whole transcriptome analysis was conducted to identify differentially expressed genes (DEGs) and to perform Gene Ontology (GO) analysis. Results Phenotypic analysis revealed significant growth enhancements in PAW-treated seedlings compared to the control group, with notable increases in seedling height, stem thickness, and biomass. Stem cross-section analysis confirmed that PAW treatment led to the enlargement of primordia tissue, leaf sheath (LS1 and LS2), and overall stem tissue area. Transcriptomic analysis revealed that 78% of the DEGs were upregulated in response to PAW, indicating that PAW acts as a positive regulator of gene expression. Gene Ontology (GO) analysis further showed that PAW treatment predominantly upregulated genes associated with transmembrane transport, response to light stimulus, oxidoreductase activity, and transcriptional regulation. Additionally, an enriched AP2/EREBP transcription binding motif was identified. Conclusion These findings suggest that PAW not only enhances sorghum seedling growth through transcriptional regulation but also has the potential to optimize agricultural practices by increasing crop yield. The upregulation of genes involved in critical biological processes underscores the need for further exploration of PAW’s potential in improving the productivity of sorghum and possibly other crops.